Respuesta :

Answer:

a.) a² + b² + c ² + 2ab + 2ac + 2bc

b.) a² + b² + c² - 2ab - 2 ac + 2bc

c ) a² + b² + c² + 2ab - 2ac - 2bc

d.) a² + b² + c² - 2ab + 2ac - 2bc

Step-by-step explanation:

  • Use ( a + b + c )² = a² + b² + c² + 2 × ab + 2 × ac + 2 × bc to expand all these expression

a) ( a + b + c )²

= a² + b² + c² + 2 × ab + 2 × ac + 2 × bc

= a² + b² + c ² + 2ab + 2ac + 2bc

b.) ( a - b - c )

= a² + ( - b )² + ( - c)² + 2a ( -b ) + 2a(-c) + 2(-b)(-c)

= a² + b² + c² - 2ab - 2 ac + 2bc

c.) ( a + b - c )²

= a² + b² + ( -c)² + 2ab + 2a ( - c) + 2 b( -c)

= a² + b² + c² + 2ab - 2ac - 2bc

d.) (a - b + c ) ²

= a² + ( -b)² + c² + 2a(-b) + 2ac + 2c( -b)

= a² + b² + c² - 2ab + 2ac - 2bc